Japan remodeled : - Vogel, Steven Kent (Cornell University Press, 2006)
he Japanese model and institutional change -- The crisis of Japanese capitalism -- Policy reform Japanese style -- The varieties of reform -- Corporate restructuring Japanese style -- The varieties of restructuring -- Japan’s new model.